Fixed Instruments to Cope with Stock Externalities An Experimental Evaluation - Gastón Giordana; Marc Willinger (Fondazione Eni Enrico Mattei (FEEM), 2007)
We evaluate the effectiveness of non optimal and temporally inconsistent incentive policies for regulating the exploitation of a renewable common-pool resource. The corresponding game is an N-person discrete-time deterministic dynamic game of T periods fixed duration. Three policy instruments with parameters that remain constant for the whole horizon are evaluated: a pigouvian tax (flat tax), an ambient tax (ambient flat tax) and an instrument combining the two previous ones (mixed flat instrument). We test in the lab the predictions of the model solved for 3 distinct behavioural assumptions: (a) sub-game perfection, (b) myopic behaviour, and (c) joint payoff maximization. We find that subjects behave myopically in the unregulated situation, which agrees with previous results in the literature. Conditional on predictions, the mixed flat instrument and the flat tax are the most effective policies in approaching the optimum extraction path. However, in absolute terms the ambient flat tax and the mixed flat instrument curb most significantly the mean extraction path towards the optimum path. Paradoxically, these instruments are the less efficient ones.
Keywords: D9; D62; H23; H26; H30; Q20; Q28; 330; Policy Instruments; Renewable Common-pool Resources; Dynamic Externalities; Experimental Economics; Gemeingüter; Erneuerbare Ressourcen; Externer Effekt; Ökosteuer; Test; Theorie